2018
DOI: 10.15406/ijh.2018.02.00049
|View full text |Cite
|
Sign up to set email alerts
|

Spring Water Quality and Human Health: An Assessment of Natural Springs of Margalla Hills Islamabad Zone-III

Abstract: Water is the earth's most valuable compound that is fundamental for humans as well as all other living forms and seems to be inexhaustible. Unfortunately the outlook for the world's fresh water supply is not very hopeful. Moreover shortage of fresh water throughout the world can be directly attributed to human misuse in the form of pollution. Water is used for number of purposes like drinking, bathing and washing etc. so it must be free from toxic materials for healthy human and aquatic life. Among surface wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…All the springs exhibit seasonal variation in Alkalinity, except Kadane spring. In this study are significantly lower than those reported by Batool et al (2018).…”
Section: Resultscontrasting
confidence: 83%
“…All the springs exhibit seasonal variation in Alkalinity, except Kadane spring. In this study are significantly lower than those reported by Batool et al (2018).…”
Section: Resultscontrasting
confidence: 83%
“…Sodium (Na + ) and potassium (K + ) are also widely used as important indicators for assessing water quality. Sodium is an essential nutrient needed by the human body for a number of functions such as muscle and nerve function, but an elevated concentration of Na + may cause a high chance of blood pressure and consequently increase the rate kidney failure (Batool et al 2018). On the other hand, although no adverse health effects have been reported to be caused by potassium intake through drinking water, it can cause an unpleasant taste and corrosion of pipes (Karavoltsos et al 2008).…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…Springs are not only a drinking source, but also a religious (shrine, sacred) place, a tourism object (religious tourism, ecological tourism, etc. ), the main water resource for irrigation, economic activities, swimming, recreation, ecological sports and serves as a place for aesthetic enjoyment of nature [2][3].…”
Section: Introductionmentioning
confidence: 99%